Un modello digitale del Piemonte con tecnologia IFSAR - Intermap Technologies, Intermap Technologies (GEOmedia, 2008)
A digital model of Piemonte with IFSAR technology The article examines a pratical application of Intermap's IFSAR surveying technology. In this context, the technology was selected by the IGM (the italian military geographical institute) in order to evaluate the radar performances in prevision of the digital mapping of the entire italian territory. The coverage of the italian territory was then provided by Intermap. The case study featured in this article deals with the coverage of Piemonte region.